The Macro Economy Today - R.Schiller Bradley (McGraw-Hill, 2009)
This textbook is quite a comprehensive of introductory macroeconomics. Great graphs, well-explained, carefully thought out. The one downside is that it is quite idealistic, as one would expect of a neo-classical economist. The author does not recognize flaws in the theories nor does he acknowledge that the real world is not so cut-and-dry and ordered as we would be led to believe. However, as stated before, this is a wonderful introductory text for anyone who wants to understand the economy today.